Low energy excitations in NiO based on a direct Δ-SCF approach. (15th November 2018) - Mackrodt, William C; Salustro, Simone; Civalleri, Bartolomeo; Dovesi, Roberto
Abstract: This paper reports calculated energies and electronic structures of nineteen excited states in NiO based on a Δ-SCF approach reported previously for the transitions in NiO and Sr2 CuO2 Cl2 . They are the spin-flip: ; eight : (one electron) 3 A2 g → 3 T 2 g, (two electron) 3 A2 g → 3 T 1 g, 3 A2 g → a 1 E g, 3 A2 g → 1 T 2 g, 3 A2 g → 1 T 1 g, 3 A2 g → b 1 E g, 3 A2 g → b 1 T 2 g ; two O(2 p ) → Ni(3 d ); seven Ni(3 d ) → O(2 p ) (including two spin-flip) and the O(2 s ) → Ni(3 d ) charge transfer excitations, which span an energy range from 0.25 eV to 17.53 eV, and include the fundamental band gap associated with an excitonic O(2 p ) → Ni(3 d ) transition at 4.23 eV. These are compared to absorption and emission spectra, and previous calculations. In the case of the O(2 p ) → Ni(3 d ) excitations, comparisons are given for gap and Γ-point energies derived from HF, PBE0, HSE06, B3LYP, B1WC, GGA and LDA one-electron approximations. Finally, the directly calculated Stokes shifts and associated luminescence energies for the two O(2 p ) → Ni(3 d ) transitions are reported, where the excitonic value is found to be in good agreement with the recently reported experimental value.